CHARACTER DEVELOPMENT OF THE NATION: A REFLECTION - Sudrajat, Jajat (International Journal of Technology And Business, 2018)
To win the competition intensifies, one of which must be strengthened is the nations character. By doing so, we can participate and win the global competition (Jokowi 2016). Character of the nation is the need for the foundation of the unity of Indonesias diverse ethnic, cultural, religious and belief. To achieve the necessary unity and cooperation of the various parties and the Government as the regulator are the main actors who play an active role. According to the Minister of Womens Empowerment and Child Protection Joanna Susana Yembise, CSR funds should be optimized to empower communities and develop the economy of local residents. Solutions to address gaps in society of justice and concern for one of them to optimize the role of educational institutions as a mediator to collaborate on a wide range of programs such as Community Development Academic, Corporate Social Responsibility (CSR), the Student Creativity Program and the activities of the Community Service Program. To map out the role of each program one of the models is needed is the Business Model Canvas (BMC).